Second‐trimester prenatal diagnosis of Nager syndrome with a deletion including SF3B4 detected by chromosomal microarray. Issue 3 (6th February 2020) - Drozniewska, Malgorzata; Kilby, Mark D.; Vogt, Julie; Togneri, Fiona; Quinlan‐Jones, Elizabeth; Reali, Lisa; Allen, Stephanie; McMullan, Dominic
Abstract: Nager syndrome is a rare, complex malformation syndrome, for which there is limited information on prenatal genetic testing. Clinical diagnosis of Nager syndrome, which can be caused by deletions encompassing SF3B4 gene, is possible prenatally. Prenatal chromosomal microarray can aid genotype‐phenotype correlation in pregnancies with structural abnormalities seen on ultrasound. Abstract : Nager syndrome is a rare, complex malformation syndrome, for which there is limited information on prenatal genetic testing. Clinical diagnosis of Nager syndrome, which can be caused by deletions encompassing SF3B4 gene, is possible prenatally. Prenatal chromosomal microarray can aid genotype‐phenotype correlation in pregnancies with structural abnormalities seen on ultrasound.